Identifying Priorities for Shark Conservation in the Bay of Bengal, Bangladesh - Badhon, Mahatub Khan; Uddin, Md Kutub; Nitu, Fahmida Khalique; Siddique, Enamul Mazid Khan (Frontiers in Marine Science, 2019)
Fisheries bycatch is known as the major threat to threatened shark species (herein, sharks, skates, and rays) in Bangladesh. But bycatch is not appropriately addressed under the existing wildlife and fisheries conservation management regime. This policy brief evaluates the current scenario of shark conservation and identifies priorities for future interventions. The literature review finds 77 shark species and only four peer-reviewed publications from Bangladesh suggesting the species already known have not yet been studied. In addition, inconsistencies in legal frameworks have limited the capacities and mandates of responsible government agencies. We recommend actionable changes in policy to regulate shark trade, reduce bycatch of threatened species, improve fisheries data reporting system, and bring consistency between institutional mandate and capacity of conservation and management agencies.